Developing Industry 4.0-Based English for Hospitality Business Learning Model - Francisca Titing Koerniawaty; Muhamad Nova (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2021)
This study aimed at developing English for Hospitality Business learning model which is adequate to Industry 4.0. This research applied the Research and Development research design. This study employed several research instruments, including a questionnaire, interview guide, observation field note, and expert judgment evaluation form. This study also invited a total number of six English lecturers and two experts on hospitality and management studies to participate in the study. As a result, a set of learning tools has been developed, including syllabus, lesson plan, and learning material. The syllabus made contains 14 learning outcomes distributed into sixteen learning topics in line with the hospitality management scope. The lesson plan developed has been arranged and organized with the combination of synchronous and asynchronous learning. The teaching and learning programs are designed for online and offline activities. The learning materials are arranged into a module covering learning materials, quiz, assignments, and discussion. The result of expert evaluation is 4.6 which can be classified as high-quality product. This learning model can be implemented for tourism vocational college, especially for hospitality management study program which needs the English subject as professional support to their career.